THE IMPACT OF THE LEAN MANUFACTURING SYSTEM ON THE COMPETITIVE ADVANTAGE OF COMPANIES - A FIELD STUDY IN INDUSTRIAL COMPANIES IN ANBAR GOVERNORATE (World Economics and Finance Bulletin, 2024)
The research aims to test the impact of the lean manufacturing system through its elements (process flow, value engineering, time management and comprehensive quality) on the competitive advantage of Iraqi industrial companies. A sample of (4) industrial companies operating in Anbar Governorate was selected to analyze the reality of the lean manufacturing system and its impact on the sustainable competitive advantage of these companies using a questionnaire form designed for this purpose. The research results concluded that a lean manufacturing system is an approach to production management that uses technology and automation to improve the flexibility and efficiency of manufacturing operations. The lean manufacturing system has several positive effects on the sustainable competitive advantage of the companies under study, and there is a need for there to be more clear attention in terms of using modern manufacturing systems, which have an important impact on the economic, social and environmental aspects of each event, whether related to the company itself in terms of its competitive value. Between other companies or related to customers or the product itself.